Antibacterial sensitizers from natural plants: A powerful weapon against methicillin-resistant Staphylococcus aureus - Li, Xiaoli; Cai, Yongqing; Xia, Qinchuan; Liao, Yongqun; Qin, Rongxin (Frontiers in Pharmacology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a drug-resistant bacterium that can cause a range of infections with high morbidity and mortality, including pneumonia, etc. Therefore, development of new drugs or therapeutic strategies against MRSA is urgently needed. Increasing evidence has shown that combining antibiotics with “antibacterial sensitizers” which itself has no effect on MRSA, is highly effective against MRSA. Many studies showed the development of antibacterial sensitizers from natural plants may be a promising strategy against MRSA because of their low side effects, low toxicity and multi-acting target. In our paper, we first reviewed the resistance mechanisms of MRSA including “Resistance to Beta-Lactams”, “Resistance to Glycopeptide antibiotics”, “Resistance to Macrolides, Aminoglycosides, and Oxazolidinones” etc. Moreover, we summarized the possible targets for antibacterial sensitizers against MRSA. Furthermore, we reviewed the synergy effects of active monomeric compounds from natural plants combined with antibiotics against MRSA and their corresponding mechanisms over the last two decades. This review provides a novel approach to overcome antibiotic resistance in MRSA.